(untitled) - Hanel, Emma Claire

Effect of feed composition and sex on feedlot performance, carcass characteristics and profitability of Dorper lambs (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.